2020
DOI: 10.1152/jn.00117.2019
|View full text |Cite
|
Sign up to set email alerts
|

A simple linear readout of MT supports motion direction-discrimination performance

Abstract: Motion discrimination is a well-established model system for investigating how sensory signals are used to form perceptual decisions. Classic studies relating single-neuron activity in the middle temporal area (MT) to perceptual decisions have suggested that a simple linear readout could underlie motion discrimination behavior. A theoretically optimal readout, in contrast, would take into account the correlations between neurons and the sensitivity of individual neurons at each time point. However, it remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…In concert with other findings [2][3][4] it evinces the likely causal role of MT neurons in motion perception, and, more broadly, provides the foundation for a robust computational framework for understanding how motion evidence is represented by neurons and transformed into a decision [5][6][7] .…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…In concert with other findings [2][3][4] it evinces the likely causal role of MT neurons in motion perception, and, more broadly, provides the foundation for a robust computational framework for understanding how motion evidence is represented by neurons and transformed into a decision [5][6][7] .…”
Section: Introductionsupporting
confidence: 55%
“…The apparently linear read-out of value signals for value-based choice indicates potential similarities to mechanisms for perceptual motion discrimination, in which a linear read-out of motion-sensitive MT cells is sufficient to explain motion judgements 3,7 . The study of perceptual decision mechanisms may therefore provide a fruitful roadmap for future experiments.…”
Section: Discussionmentioning
confidence: 93%
“…The spiking activity of a simultaneously recorded population of neurons has also been used to predict the animals' focus of attention and behavior in a single trial Maunsell 2010, 2011). Since handling high-dimensional data is difficult, many studies have devised methods to obtain a onedimensional metric from a high-dimensional dataset to predict behavior (Cohen and Maunsell 2010;Cunningham and Yu 2014;Yates et al 2020). Using a simple method of projecting trials onto a one-dimensional axis constructed using the mean spiking activity of a neuronal population of two different attention conditions (Cohen and Maunsell 2010;Mayo et al 2015), Mayo and Maunsell (2016) showed that the projections of neutral cueing condition were also intermediate between cued and uncued conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For simplicity, in this toy example, we assume there is no structure in the co-variability that can be exploited for decoding. In this case, increased variability along the stimulus axis (the so-called information-limiting noise) will change the amount of information about the stimulus, while, importantly, variability orthogonal to the stimulus axis will not [19,[22][23][24][25]. We call this variability direction the "non-stimulus axis" (Fig 1A).…”
Section: Introductionmentioning
confidence: 99%